2013
DOI: 10.1124/dmd.113.053108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ritonavir on Human CYP2B6 Catalytic Activity: Heme Modification Contributes to the Mechanism-Based Inactivation of CYP2B6 and CYP3A4 by Ritonavir

Abstract: The mechanism-based inactivation of human CYP2B6 by ritonavir (RTV) in a reconstituted system was investigated. The inactivation is time, concentration, and NADPH dependent and exhibits a K I of 0.9 mM, a k inact of 0.05 min 21, and a partition ratio of approximately 3. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis showed that the protonated molecular ion of RTV exhibits an m/z at 721 and its two major metabolites are an oxidation product with MH + at m/z 737 and a deacylated product with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 46 publications
2
30
3
Order By: Relevance
“…The integrity of the CYP3A4 heme chromophore after incubations with ritonavir suggest that inactivation occurs through a mechanism independent of heme destruction. This is contrary to the recent article by Lin et al, (2013) where the authors report finding that ritonavir inactivation of CYP3A4 was attributable to heme destruction with the formation of a heme-protein adduct, and no significant modification of the apoprotein. The report of Inactivation of CYP3A4 by Ritonavir heme destruction and a heme-protein adduct were performed with reconstituted CYP3A4 and P450 reductase, in comparison with the studies performed here in both CYP3A4 Supersomes and reconstituted 3A4 enzyme with reductase and cytochrome b 5 .…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The integrity of the CYP3A4 heme chromophore after incubations with ritonavir suggest that inactivation occurs through a mechanism independent of heme destruction. This is contrary to the recent article by Lin et al, (2013) where the authors report finding that ritonavir inactivation of CYP3A4 was attributable to heme destruction with the formation of a heme-protein adduct, and no significant modification of the apoprotein. The report of Inactivation of CYP3A4 by Ritonavir heme destruction and a heme-protein adduct were performed with reconstituted CYP3A4 and P450 reductase, in comparison with the studies performed here in both CYP3A4 Supersomes and reconstituted 3A4 enzyme with reductase and cytochrome b 5 .…”
Section: Discussioncontrasting
confidence: 56%
“…Ritonavir is also reported to be a tight, irreversible binding inhibitor of CYP3A4 via coordination to the heme iron (Sevrioukova and Poulos, 2010). More recently, ritonavir has been reported to cause heme destruction in a reconstituted CYP3A4 system (Lin et al, 2013). Together, these reports suggest that multiple mechanisms of bioactivation and inhibition may occur with ritonavir and CYP3A4.…”
Section: Introductionmentioning
confidence: 70%
“…19,20 In agreement with previous in vitro studies two metabolites of ritonavir were detected in urine extracts (the oxidised and deacylated products), however the glutathione conjugate was not detected and this metabolite may have preferentially been excreted by the biliary route. 15 The detection of a number of metabolites of atazanavir and darunavir in this study agreed with previous work showing that these pharmaceuticals are extensively metabolised in humans via oxidation, carbamate hydrolysis, deacylation (atazanavir) and glucuronidation (darunavir). 16,17 The ability to detect the parent cART drugs and a wide range of their transformation products in urine extracts suggest that in future studies, links between pharmacogenetics, metabolism and drug efficacy could be investigated, which may lead to a more personalised approach to cART intervention.…”
Section: Metabolism Of Cart Drugssupporting
confidence: 92%
“…Identification of the metabolites was supported by fragmentation patterns which were compared to those of metabolite structures that had already been detected in rodent urine, human blood and hepatocyte studies. [15][16][17][18] Analysis of the OPLS-DA loadings plot for each cART parent compound confirmed that all but one urine sample contained cART drugs at the time of sample donation. As none of the parent drugs nor any of their metabolites were detected in urine extracts from this patient in the darunavir group, this sample was excluded from further statistical analyses.…”
Section: Identification Of Cart Drugs and Metabolitesmentioning
confidence: 81%
“…This may relate to effects of ritonavir or lopinavir on nuclear receptors and their regulation of CYPs 2B6 and 3A, and P-gp (Svärd et al, 2010). Relationships of these clinical observations to mechanism-based inactivation of CYPs by ritonavir are presently unknown (Lin et al, 2013).…”
Section: Controlmentioning
confidence: 99%